Demographic trends in Portuguese-speaking countries in Sub-Saharan Africa - Morkusová, Andrea; Miskolczi, Martina; Dotlačilová, Petra; Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky (2013)
The aim of the thesis is to analyze the demographic trends between years 1960 and 2010 of the Lusophone countries in Sub-Saharan Africa, namely in Angola, Mozambique, Cape Verde, Guinea-Bissau, Sao Tomé and Príncipe and Equatorial Guinea and more, to comment possible future development until 2050. In these countries, fertility and mortality have been quickly decreasing while the proportion of people's literacy grows. The total fertility rate in these countries is currently between 4 and 5.5 children per woman with exception of Cape Verde, where the value reaches only 2.4 children per woman. The highest mortality rate is registered in Mozambique and the lowest one in Cape Verde. Literacy increased from the lowest value of 20 % in Guinea-Bissau in 1960 to the highest value of 94 % in Sao Tomé and Príncipe and in Equatorial Guinea in 2010. Among others, HIV prevalence is presented as well as it has influence upon demographic and economic development of selected countries.
Vedoucí práce: Martina Miskolczi
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky, 2013
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2013
Způsob přístupu: Internet
Keywords: sociálně ekonomická demografie [obor bakal. práce]; bakalářské práce; bachelor's theses